Fast-rotating blue straggler stars in the globular cluster NGC 1851 - (:unkn) unknown (EDP SCIENCES S A, 2026)
We studied the rotational velocities of a sample of blue straggler stars (BSSs) and reference stars belonging to the Galactic globular cluster NGC 1851 using high-resolution spectra acquired with FLAMES-GIRAFFE at the ESO/VLT. After field decontamination based on radial velocities and proper motions, the final sample of member stars was composed of 15 BSSs and 45 reference stars populating the red giant and horizontal branches of the cluster. In agreement with previous findings, the rotation of the reference stars is negligible in general (lower than 15 km s(-1)). In contrast, the rotational velocity is high (up to similar to 150 km s(-1)) for a subsample of BSSs. We found 4 fast-rotating BSSs (defined as stars that spin faster than 40 km s(-1)), which corresponds to a percentage of 27 +/- 14%. This result delineates a monotonically decreasing trend (instead of a step function) between the percentage of fast-spinning BSSs and the central concentration and density of the host cluster. This supports a scenario in which recent BSS formation preferentially occurs in low-density environments from the evolution of binary systems.
Keywords: techniques: spectroscopic; blue stragglers; stars: rotation; globular clusters: general